Interplay Between the N-Terminal Domains of Arabidopsis Starch Synthase 3 Determines the Interaction of the Enzyme With the Starch Granule - Gámez-Arjona, Francisco M.; Mérida, Ángel (Frontiers in Plant Science, 2021)
The elongation of the linear chains of starch is undertaken by starch synthases. Class 3 of starch synthase (SS3) has a specific feature: a long N-terminal region containing starch binding domains (SBD). In this work, we analyze in vivo the contribution of these domains to the localization pattern of the enzyme. For this purpose, we divided the N-terminal region of Arabidopsis SS3 in three domains: D1, D2, and D3 (each of which contains an SBD and a coiled-coil site). Our analyses indicate that the N-terminal region is sufficient to determine the same localization pattern observed with the full-length protein. D2 binds tightly the polypeptide to the polymer and it is necessary the contribution of D1 and D3 to avoid the polypeptide to be trapped in the growing polymer. The localization pattern of Arabidopsis SS3 appears to be the result of the counterbalanced action of the different domains present in its N-terminal region